ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN 107 TENTANG IJARAH PADA PT AL-IJARAH INDONESIA FINANCE SAMARINDA - NONIS LESMANA PUTRI; ISNA YUNINGSIH; MUSVIYANTI - (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
This research aims to analyze the application of ijarah financing accounting at the Sharia Multi-Purpose Leasing Al-Ijarah Indonesia Finance Samarinda. whether it is suitable or not with the Statements on Financial Accounting Standard or PSAK Number 107 on Ijarah Accounting. The Problem ini this research is formulated as follows  :” Does the application of ijarah financing accounting at the Sharia Multi-Purpose Leasing Al-Ijarah Indonesia Finance Samarinda follow the statements on Financial Accounting Standard or PSAK Number 107 on Ijarah Accounting?”   The instrument used to analyze the data in this research was the Statements on Financial Accounting Standard or PSAK Number 107 on Ijarah Accounting.  Based on the research finding, it is concluded that Sharia Multi-Purpose Leasing Al-Ijarah Indonesia Finance Samarinda did not fully follow the statements on Financial Accounting Standard or PSAK Number 107 on Ijarah Accounting.Keywords: Sharia Accounting, Ijarah, PSAK Number 107